2013
DOI: 10.1080/17470919.2013.807300
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence correlates with functional responses to dynamic changes in facial trustworthiness

Abstract: Emotional intelligence (EI) refers to a constellation of traits, competencies, or abilities that allow individuals to understand emotional information and successfully navigate and solve social/emotional problems. While little is known about the neurobiological substrates that underlie EI, some evidence suggests that these capacities may involve a core neurocircuitry involved in emotional decision-making that includes the ventromedial prefrontal cortex (vmPFC), anterior cingulate cortex (ACC), insula, and amyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 57 publications
2
30
1
Order By: Relevance
“…In contrast to our previous neuroimaging studies on EI [9,10], no associations between EI and activation within the vmPFC and amygdala were found. This discrepancy is most plausibly accounted for by the present use of backward masking (vs. overt perception), which has been shown to bypass higher cortical processing.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…In contrast to our previous neuroimaging studies on EI [9,10], no associations between EI and activation within the vmPFC and amygdala were found. This discrepancy is most plausibly accounted for by the present use of backward masking (vs. overt perception), which has been shown to bypass higher cortical processing.…”
Section: Discussioncontrasting
confidence: 85%
“…All participants provided written informed consent. Partial data from this sample have been reported elsewhere [7,10], but the associations between EI and maskedanger responses are novel and have not previously been published. This research protocol was reviewed and approved by the Institutional Review Board of McLean Hospital and the US Army Human Research Protections Office.…”
Section: Participantsmentioning
confidence: 84%
See 1 more Smart Citation
“…The insula is also involved in interoceptive processing (Craig, 2003), emotional forms of empathy (Gu et al, 2012), and emotion regulation (Goldin et al, 2008;Ochsner & Gross, 2005;Ochsner et al, 2004). In relation to trust, there is evidence that the insula is involved in modifying trust-based decisions (Adolphs, 2002;Castle et al, 2012;Dimoka, 2010), and some recent studies have shown that the insula plays roles in both trust (Killgore et al, 2013) and distrust (Winston et al, 2002). Together, these findings indicate that the insula may facilitate negative emotion attribution and heightened arousal when forming negative interpersonal social attitudes about others.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that faces expressing positive emotions, such as a smiley face, were more likely to be trusted, while those expressing negative emotions, such as an angry face, were less likely to be trusted [5]. Furthermore, viewing a less trustworthy face stimulated brain areas, such as the amygdala, that are involved in emotions and caused unpleasant emotions toward the other person [4,16]. In the present study, when linguistic information and a facial expression were congruent, a negative face made the other person feel more unpleasant, have decreased trust, and donate a significantly smaller amount of money.…”
Section: Discussionmentioning
confidence: 99%